KETERAMPILAN BERPIKIR KRITIS MAHASISWA DALAM MEMECAHKAN MASALAH MATEMATIKA BERDASARKAN KETERAMPILAN ABAD 21 - Muzayyanatun Munawwarah; Nurul Laili; Mohammad Tohir (Alifmatika (Jurnal pendidikan dan pembelajaran Matematika), 2020)
Descriptive analysis methode of research describes about increasing subject in the level of critical thinking skills of students in solving mathematics based on 21st-century skills. The subjects research were 28 students of Mathematics Education Study Program at Ibrahimy University of Situbondo. Data collection is done by providing pre-test and study documentation to students. The test is given to collect data related to students' critical thinking skills. Then learning is done based on 21st-century skills. Furthermore, students are given a post-test solving mathematical problem. Data were collected through observations, test results and interview data tested for their validity by triangulation. The data analysis technique used is qualitative descriptive data analysis. The results of this study indicate that: (1) the results of the achievement of indicators of critical thinking of students based on critical thinking stages formulated by Facione, overall the subject of an increase of 7.53%; (2) there was the same highest increase in the achievement of the indicator thinking Facione stage, namely at the Analyze stage (A) for high, medium, and low category subjects respectively, 77.78%, 80%, and 44.44%. However, there are still two stages of critical thinking that still need attention for further research, namely at the List (L) and Self-Correct (S) stages classified as still needing special attention in implementing 21st-century skills in learning activities; (3) the level of critical thinking skills of students based on the critical thinking stages formulated by Facione was in the category of "not critical" for the pre-test results and was in the category of "sufficient critical" for the post-test results.